The Dilemma of Upholding ASEAN’s Principle of Non-Interference in the Case of Myanmar Political Crisis - Prayitno, Heru (Technium Social Sciences Journal, 2022)
The political crisis that has happened in Myanmar since the February 2021 coup has not ended and has even caused social unrest and casualties. ASEAN is faced with a difficult dilemma, particularly on the implementation of the principle of non-interference. It was noted that ASEAN decided not to invite Myanmar representatives, but only non-political representatives, to the ASEAN Summit. The decision is quite surprising given that ASEAN has always prioritized the principle of non-interference in the member countries' domestic problems and makes ASEAN was seen as having reneged on its principles that have been upheld since its formation. The paper argues that the principle of non-interference is not abandoned, but ASEAN rather puts forward other principles to help resolve the problems of one of its family members. This paper also examines how ASEAN copes with the political crisis in Myanmar, including whether the decision not to include Myanmar from the ASEAN Summit is effective. ASEAN needs to urge Myanmar to immediately implement the Five-Points Consensus that has been mutually agreed upon, and Cambodia has the opportunity to show the world that its chairmanship for 2022 will provide a legacy in resolving the Myanmar political crisis.